Fluid Measure and Disbursement: Valuation of a Closely-Held Firm - William P. Dukes (Journal of Small Business Finance, 1995)
There are about 24 million businesses in the United States, with something less than one-tenth of one percent actively traded. This case is hypothetical, but the valuation issues pertaining to many of those closely-held firms are real. The case illustrates an income statement adjustment, estimation of a required rate of return, application of discounts to an "as if actively traded” price, and valuation treatment of excess assets not needed in the operation of the firm. The desire for market data is clear, but for closely-held firms market data must be proxied by the best available information and applied to sometimes less than complete information pertaining to valuation issues for closely-held business. Some of these techniques are applied in the solution of the case.
Keywords: G32; 650; Fluid Measure; Disbursement; Valuation; Small Business; Closely-Held